Antepartum Diagnosis and Management of Lamin A/C Disease - Nosheen Reza; Jessica L. Chowns; Amy Marzolf; Jessica Kim; Lisa D. Levine; Gregory Supple; Anjali Tiku Owens (Case Reports in Cardiology)
Lamin A/C cardiac disease is a genetic cardiomyopathy and arrhythmia syndrome caused by alterations in the function of the nuclear lamin A and C proteins. It is inherited in an autosomal dominant manner and usually presents in mid- to late adulthood with atrioventricular conduction abnormalities, atrial and ventricular arrhythmias, biventricular dysfunction, and advanced heart failure. While rare, women of childbearing age can exhibit an aggressive disease course, and appropriate risk stratification and management are critical. Here, we present a case of newly diagnosed lamin A/C cardiac disease in a pregnant woman.